PENGARUH PEMBERIAN PENYULUHAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN TENTANG ANEMIA PADA SISWI DI MADRASAH ALIYAH PONPES ALI MAKSUM KRAPYAK BANTUL YOGYAKARTA - Susilo Rini; Yunia Kesyanto (Viva Medika, 2010)
Background: In the Special Region of Yogyakarta showed the highest incidence of anemia on the basis of the data Central Statistics Agency (BPS) in 2008, mostly in the districts of Bantulis 11 195 (82.07%), Sleman as many as 11 104 (81.64%), Kulonprogo 5713 (74.12%),Mountains south of 7626 (72.81%), and the city 3527 (68.69%), anemia in Bantul increasefrom year 2008 to year 2009 to 80.02%. Iron deficiency anemia can cause various effects onyoung women, among others, lowering the immune system so prone to disease, decreasedactivity and academic achievement. Objective: To determine the effect of health education to increase knowledge about anemia ingirls and boys in Ponpes Ali Maksum Krapyak Bantul Yogyakarta. Research Methodology: The type of analysis is an experiment. The method used Pretestposttest With Control Group. The sample in the study were students at Madrasah Aliyah AliMaksum Krapyak Ponpes counted 134 people in Bantul Yogyakarta. The data analysis usesindependent t-test. Results: The results obtained in this study is that after the extension of anemia most girls atAli Maksum Krapyak Ponpes Bantul Yogyakarta has a good knowledge of 30.6% in thecontrol group, and 39.6% in the experimental group. Research Conclusions: Based on analysis test found no significant effect on the provision ofhealth education to increase knowledge about anemia in girls and boys in Ponpes AliMaksum Krapyak Bantul Yogyakarta. Keywords: Anemia, Knowledge-pretest-posttes